THE HISTORY OF THE CREATION OF "RAWZAT AS-SAFA" BY HISTORIAN MIRKHOND - Uralov Khaitboy (American Journals Publishing, 2023)
In this article, the famous work "Rawzat al-Safa" created by the historian Mirkhand, who created in the 15th century, describes the socio-economic, political and cultural history of Movarounnahr and Khurasan from the creation of mankind to the Timurid period, in which the geographical place names of Movarounnahr and Khurasan, information about rivers, mountains and deserts is given.
Keywords: Central Asia, Middle East